Lessons Emerging from Curriculum Practices - Khader, M. A. (Voices of Teachers and Teacher Educators, 2017)
This article rests on the premise that activities form the source of learning experience. It outlines the key ideas gained by the author during his participation in the formulation and implementation of National Curriculum Framework(2005) and Kerala Curriculum Framework(2007). The ideas centering on the connectivity of curriculum and, individual and society, and the different meanings of process perspective are outlined here. Illustration of theorising of specific instances observed during curriculum implementation, as well is another feature. This speaks of the meaning of experience and adds on to the richness of curriculum.